Identification of perturbations of the ionospheric plasma parameters by the probe measurements on the satellite "Sich-2" - Shuvalov, V.A.; Pilipenko, O.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
By the results of probe measuring of the ionospheric plasma parameters by the ITM’s equipment on the spacecraft "Sich-2", it is shown that perturbations of the concentrations of charged (electrons, ions) particles and the temperatures of heavy (neutrals, ions) particles could be used, considering the subsatellite point dynamics, for the identification of the spatio-temporal location of the volcano eruptions, epicenters and magnitudes of the inceptive earthquakes, and for the localization of the North and South auroral peaks in the Earth’s ionosphere.